Analisis Wacana Kritis Trash-talk Pada Konten Game Mobile Legends Di Kanal Youtube Gerrard Wijaya - Ferdyanto Tantyo Nugroho; Syafrida Nurrachmi Febriyanti (Jurnal Ilmiah Wahana Pendidikan, 2023)
The use of Trash-talk on the Youtube platform or in the play environment of generation Z youth is a phenomenon that is commonly seen, but it is interesting to see the use of Trash-talk which was originally a ban for parents to their children but has become normalized in the surrounding environment. The data collection technique was carried out by means of documentation studies and observations of Game Content entitled "DADADADADADAR ML RASA PUBG" owned by Gerrard Wijaya's Youtube Channel. The data analysis technique used is critical discourse analysis using the Van Dijk model which describes three dimensions, namely text, social cognition and social context. The results of this study are divided into three parts based on aspects of the text that give rise to Trash-talk representations, social cognition that explains the reasons for content creators producing texts, and social contexts that connect the meaning of power to discourse in society.